Trajectories of a magnetic sphere in a shaken three-dimensional granular bed under low gravity - Ke Cheng; Meiying Hou; Wei Sun; Zhihong Qiao; Xiang Li; Tuo Li; Mingcheng Yang (Scientific Data)
Abstract This present investigation employs an advanced magnetic particle tracking method to trace the trajectories of an intruder within a vibration-driven granular medium under artificial low-gravity conditions. The experiments are carried out within the centrifuge of the Chinese Space Station, encompassing six distinct low-gravity environments. Trajectories under various vibration modes are captured and analysed for each gravity level. This paper offers an exhaustive account of data collection and algorithms used for data processing, ensuring the dependability and precision of the datasets obtained. Additionally, we make the raw magnetic field data, processing scripts, and visualization tools accessible to the public. This research contributes a comprehensive dataset that is instrumental in exploring the mechanisms of granular segregation under low gravity and aids in the verification of novel physical models for understanding intruder dynamics in granular systems under such conditions.